Bargaining Units and Bargaining Power - Forrest, Anne (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This paper examines how the recent amendment to the Labour Relations Actestablishing compulsory first contract arbitration in Ontario fits within the existing legal framework.